RITUALISASI KESENIAN BARONG DALAM ESTETIKA BUDAYA: STUDI EKSPLORATIF KOMUNIKASI INTRA PERSONAL MASYARAKAT KOTA BERIBADAT - Djaya, Tika Ristia (Universitas Medan Area, 2020)
The purpose of this research is to find out how barong performers perform rituals, people's responses to rituals performed by barong players and the effect of rituals on the personal behavior of barong singers in Kencono in Kendal, Central Java. This study uses a qualitative method with an exploratory approach. The results of the study showed that the rituals performed by barong players included lek-lekan at night before the performance and accompanied by recitation, using offerings such as market snacks, bananas, flowers and eggs. Modern society interprets the offerings as art in culture, not the flow of beliefs that are believed to be guidelines for the belief in their lives. The ritual does not cause a negative influence on the barong player but instead increases devotion to God Almighty. Singo Kencono's barong art was formed to reflect the culture even though there have been many changes in accordance with the times but it still does not eliminate the original culture, other than that Singo Kencono's barong art was formed and played to entertain the public.